EFFECTS OF GROUNDWATER DEVELOPMENT ON THE ENVIRONMENT - Custodio, Emilio (Águas Subterrâneas, 2000)
Groundwater is an essential part of the hydrological cycle. It is characterized by its long turnover time, ubiquity and small variability. Flow and chemical characteristics and properties have to be considered in a three dimensional framework. Groundwater stable flow and definite chemical character play a key role in geological and biological processes and thus has significant environmental implications in maintaining river and spring base flow, wetlands, phreatophyte communities, gallery forest, ..., and also is an essential feature in favour of its development. Groundwater development implies a change in the flow pattern which may result in water table lowering, decrease of outflow and chemical changes, moveover land subsidence in some cases. All this modifies environmental conditions, which leads to water flow decrease, reduction of phreatophyte surface area, wetland desiccation and biological modifications related to chemical changes. But these changes appear with a long delay and at a slow pace. Thus the cause-effect relationships are not always evident. Negative impacts have to be compared with the benefits derived from development and with the impacts of other alternatives. This includes the consideration and the cost of possible correction of the long delayed negative effects. Aquifer salinization and contamination is an important environmental issue that has to be taken into account since groundwater will be soon or later discharged into the environment, carrying with it the contaminants or their transformation products, in a complex way.